Developing Learning Tools (LKPD) fCapillarity Material Based on the Context of Bioactivator in Peanut Planting Media to Improve Students' Scientific Literacy - ; Desi Ariani (Syntax Idea)
This research aims to develop a Student Worksheet (LKPD) based on capillarity material by utilizing the context of bioactivators in peanut planting media, with a focus on increasing students' scientific literacy. Capillarity material is a relevant topic in science learning, and the use of bioactivators in the context of peanut farming provides real relevance to students' daily lives. The research method used is Research and Development (R&D) with stages of development, validation and limited trials. Data was collected through observation, interviews, and students' scientific literacy tests. The research results show that the LKPD developed has a high level of quality, complies with scientific literacy guidelines, and is able to increase students' understanding of the concept of capillarity. This research makes an important contribution to the development of science teaching materials that are more contextual and relevant to students' daily lives. In addition, increasing students' scientific literacy is also expected to help them develop critical and analytical thinking skills that are important in the world of modern science.